KAJIAN PENEMPATAN LOKASI BANGUNAN PENGENDALI SEDIMEN (CHECK DAM) DAS TAPIN - Rahmawati Rahmawati (Teknika, 2021)
Sediment is material that is carried away and moves in the direction from flow of river water and settle downstream of a watershed. Changes in land use in the upstream watershed have the potential to increase sediment. Then, the increase in population will be proportional to the increasing need for land both for settlement and agriculture so that forest land will be looted and increase sedimentation. To overcome these problems, it is necessary to study the placement of sediment control buildings or check dams. Sedimentation is influenced by the amount of erosion. Erosion and sedimentation analysis were analyzed using Arc SWAT and from the results of the erosion analysis in the Tapin watershed, the average heavy class is less than 180 tons. Changes in sedimentation value from the dam plan to the present are 1.6 mm/yr until 1.8 mm/yr. Analysis used for selection of check dam locations is AHP (Analytical Hierarchy Process) Expert Choice. From the analysis of the selection of priority check dam locations Sub Watershed 1. The design flood discharge analysis for Q 50 years that uses ITB-2 method is 41.34 m3/second. The hydraulic aspect of the check dam in Sub watershed 1 is adjusted to the existing cross section of the river and prevous analysis, the results of analysis of sediment inflow are 6.592,05 m3/year and storage capacity is 49.132,00 m3, namely the building height is 3.75 meters.